An officer and a Fortune - Crespo, Nina, 1967- (Fortunes of Texas. Hotel Fortune., 2021)
"Captain Collin Waldon is on leave from the military, tending to his ailing father in his final days. Knowing his stay in Rambling Rose will be short, Collin is not looking for romantic entanglements--especially not with Nicole Fortune, the beautiful, free-spirited executive chef of Roja Restaurant in the struggling Hotel Fortune. Yet these two unlikely lovers seem perfect for each other, until Collin's reassignment threatens their newfound bliss..."--